Molecular Pathways: Involving Microenvironment Damage Responses in Cancer Therapy Resistance - Sun, Yu (2012)
The armamentarium of therapeutics used to treat cancer patients relies heavily on ionizing radiation and chemotherapeutic drugs that severely damage DNA. The responses of tumor cells to these treatments is heavily influenced by their environment: physical contacts with structural elements such as extracellular matrix, associations with resident and transitory benign cells such as fibroblasts and leukocytes, and interactions with numerous soluble endocrine and paracrine-acting factors all modulate tumor cell behavior. Importantly, this complex tumor microenvironment is not static and dynamically responds to a variety of stimuli. Here, we describe emerging data indicating that genotoxic cancer treatments activate highly conserved damage response programs in benign constituents of the tumor microenvironment. These damage signals, transmitted via master regulators such as NFkB, culminate in a powerful and diverse secretory program that generates a pro-angiogenic, pro-inflammatory microenvironment. Constituents of this program include Interleukin (IL)-6, IL-8, hepatocyte growth factor, amphiregulin, matrix metalloproteinases, and other factors demonstrated to promote adverse tumor cell phenotypes including enhanced resistance to treatment and rapid tumor repopulation. A detailed understanding of these survival signals induced in the context of genotoxic stress provides a platform to develop combinatorial strategies to improve outcomes that consider malignant cells, the tumor microenvironment, and the dynamics exerted by the treatment itself.